The Influence of Tinnitus on the Audiometric Threshold of Sufferers - Ukaegbe,Onyinye (2016)
Abstract Introduction Tinnitus is a worldwide problem. Objective The objective of this study is to evaluate the audiometric hearing thresholds of adult patients with ongoing tinnitus as their only otological symptom. Methods We evaluated the hearing thresholds of 43 adult patients with ongoing tinnitus and no history of hearing loss from the otolaryngology department of a tertiary health institution at speech and high frequencies. A total of 56 tinnitus ears were compared against 30 contralateral normal ears as well as with the 100 ears of 50 healthy volunteers. Results The study group consisted of 11 (25.6%) males and 32 (74.4%) females with a mean age of 40.9 11.7. The mean Pure Tone Average of the 56 tinnitus ears was 14.8 9, while that of the 100 control ears was 11.2 6 (U 1/4 2078, p= 0.008). The mean pure tone average of the control was also significantly lower than that of the 30 contralateral normal ears of the tinnitus sufferers (U 1/4 1136, p= 0.02). We observed mild to moderate hearing loss in 10 (23%) of the participants. We observed no hearing loss among the control group. Conclusion A proportion of tinnitus sufferers with self-professed normal hearing are likely to have mildly elevated pure tone audiometric thresholds. In patients with unilateral tinnitus, such elevated pure tone hearing thresholds are likely to be in the tinnitus ear and the contralateral non-tinnitus ear.